Green Loans dan Sustainable Profitability: Peran Moderasi Kepemilikan Institusional - Citta Anggula Franconnie; Agung Juliarto (Diponegoro Journal of Accounting, 2026)
This research analyzes the impact of green loans on sustainable profitability within banking companies, while considering institutional ownership as the moderating factor. The research examines the banking sectors in Indonesia, Malaysia, Singapore, Thailand, and Germany from 2020 to 2024 by employing a cross-country approach utilizing purposive sampling. A total of 106 observations were gathered from Bloomberg, financial statements, and sustainability reports, and then examined using Moderated Regression Analysis (MRA). The results indicate that green loans have a notably adverse impact on sustainable profitability, which is opposite to the hypothesis put forward. Additionally, institutional ownership plays a significant and positive role in enhancing the relationship.